Pattern of disease-modifying therapies use and related adverse events among multiple sclerosis patients (Brazilian Journal of Pharmaceutical Sciences, 2024)
This study attempted to describe the disease modifying therapies (DMTs) use patterns and related adverse events in multiple sclerosis (MS) patients assisted by the Brazilian Unified Health System (SUS). This is a cross-sectional study conducted at a reference center in the Midwestern Brazil. Demographic, socioeconomic, and clinical data, and adverse events associated with DMTs were collected. We observed 291 patients with a mean age of 41.4 years, and mostly (68.6%) women. Most patients (58.8%) were using first-line treatment. Fingolimod (29.9%) and beta interferons (23.7%) were the most used drugs. About 74.2% of patients used DMTs for more than six months. In 26.5% of patients, 238 adverse events were reported, 67.2% of which were mild and 32.8% of which were moderate. The most frequent adverse events were headaches (6.9%), myalgia (3.8%), and flu-like symptoms (3.1%). The proportion of adverse events proportion ranged from 17.3% (natalizumab) to 41.2% (dimethyl fumarate). Most MS patients treated by SUS used first-line DMTs. After adjustment, there was noticed that adverse events associated with DTMs are twice as likely to occur in users of the first-line treatment than other lines (OR 1.99, p=0.01). It is essential to develop DMTs safety monitoring strategies to promote their rational use.